The role of Elateriospermum tapos yoghurt in mitigating high-fat dietary cause of maternal obesity—an experimental study - Naomi, Ruth; Rusli, Rusydatul Nabila Mahmad; Othman, Fezah; Balan, Santhra Segaran; Abidin, Azrina Zainal; Embong, Hashim; Teoh, Soo Huat; Jasni, Azmiza Syawani; Jumidil, Siti Hadizah; Bahari, Hasnah; Yazid, Muhammad Dain (Frontiers in Endocrinology, 2023)
Maternal obesity is the key predictor for childhood obesity and neurodevelopmental delay in the offspring. Medicinal plants are considered to be the safe and best option, and at the same time, probiotic consumption during pregnancy provides beneficial effects for both the mother and the child. Current research has shown that Elateriospermum tapos (E. tapos) yoghurt is safe to consume and consists of many bioactive compounds that can exert an anti-obesity effect. Thus, this study has been designed to study the role of E. tapos yoghurt in mitigating maternal obesity. In this study, a total of 48 female Sprague Dawley (SD) rats were assigned to six groups, with eight rats per group, and obesity was induced over 16 weeks with a high-fat diet (HFD) pellet. On the 17th week, the rats were allowed to mate and pregnancy was confirmed through vaginal smear. The obese induced group was further divided into negative and positive control groups, followed by E. tapos yoghurt treatment groups with three different concentrations (5, 50, and 500 mg/kg). The changes in body weight, calorie intake, lipid profile, liver profile, renal profile, and histopathological analysis were measured on postnatal day (PND) 21. The results show that the group with the highest concentration of E. tapos yoghurt (HYT500) supplementation shows gradual reduction in body weight and calorie intake on PND 21 and modulates the lipid level, liver, and renal enzymes to a normal level similar to the normal group. In histological analysis, HYT500 reverses the damage caused by HFD in liver and colon, and reverses the adipocytes’ hypertrophy in retroperitoneal white adipose tissue and visceral fat. In conclusion, supplementation of E. tapos yoghurt during the gestational period up to weaning is effective in the gradual weight loss of maternal obese dams from the 500-mg/kg-supplemented group in this study.